ANALISIS STRATEGI AKTUALISASI DIRI SASYA TRANGGONO PEREMPUAN PERUPA INDONESIA DALAM MASA PANDEMIK COVID-19 - Adriati, Ira (Jurnal Budaya Nusantara, 2021)
Sasya Tranggono is an Indonesian female artist who works with the subjects of puppets, flowers and butterflies. Her work is well known in the Indonesian art social scenes; she has actualized herself. In this research condition analyzes the self-actualization process during the Covid-19 pandemic. This research is a qualitative research. Using Abraham Maslow's theory of self-actualization which has been converted to fine arts, Hans Van Maneen's theory for the exhibition process, and Hennessy's theory relating to publication on social media. Based on the analysis, it can be seen that Sasya Tranggono tries to maintain her self-actualization even through social media such as Instagram and the web. She has collaborated with several galleries to exhibit her work online and offline. All of her publication strategies kept her at the pinnacle of self-actualization.